Ultrathin Metal–Organic Framework Nanosheets as Nano‐Floating‐Gate for High Performance Transistor Memory Device. (2nd December 2021) - Shi, Naien; Zhang, Jun; Ding, Zhen; Jiang, Hui; Yan, Yong; Gu, Daqing; Li, Wen; Yi, Mingdong; Huang, Fengzhen; Chen, Shufen; Xie, Linghai; Ren, Yubao; et al.
Abstract: Metal–organic framework (MOF) is an emerging important class of functional materials in the fields of information storage, wearable electronics and optoelectronic devices. The interaction of electrons or holes with MOFs is important for the systematic exploration of MOFtronics and to investigate the related structure–performance correlation. Herein, MOF flat nanosheets of copper tetrakis(4‐carboxyphenyl)porphyrin with sub‐10 nanometer scale in thickness are employed as the charge‐trapping layer in organic field‐effect floating‐gate transistor memory device fabricated by an air–liquid interfacial assembly and subsequent stamping operation. As charge trapping sites, MOF nanosheets with ultrathin nanoporous arrays significantly improve in comparison with the memory device using its counterpart ligand of tetrakis(4‐carboxyphenyl)porphyrin as the trapping elements. As compared to the reported widely applied nanofloating gate materials of gold nanoparticles, graphene, or macromolecular nanomaterials, a short pulse (≈ 20 ms) on the device gets a considerable memory window of ≈ 37.5 V at a programming voltage of ‐ 80 V, with a retention time longer than 10 4 s and good ON/OFF ratio of > 10 3 . Furthermore, the hybrid structure composed of metal and organic components endows it with electron and hole trapping capability. This work could push forward the fundamental research of organic–inorganic–hybrid electronics in future microelectronic research. Abstract : The interactions of electrons or holes with metal–organic frameworks (MOFs) are important for the systematic exploration of MOFtronics and investigation of the related structure–property correlation optimization. Herein, ultrathin copper tetrakis(4‐carboxyphenyl)porphyrin nanosheets exhibit good electron and hole trapping capability superior to its ligand tetrakis(4‐carboxyphenyl)porphyrin and ranks high in current nanofloating gate materials.